Obinutuzumab in Combination with Alternative Chlorambucil Schedules in Front-Line Treatment of Chronic Lymphocytic Leukemia: A Study by KroHem, the Croatian Cooperative Group for Hematologic Diseases - Igor Aurer; Ozren Jakšić; Sandra Bašić-Kinda; Karla Mišura-Jakobac; Jasminka Sinčić-Petričević; Sabina Novaković-Coha; Davor Galušić; Hrvoje Holik; Toni Valković; Dubravka Županić-Krmek; Ida Hude-Dragičević; Vibor Milunović; et al. (Biomedicines)
Background/Objectives: Obinutuzumab was approved for front-line treatment of chronic lymphocytic leukemia in combination with chlorambucil pulses administered every 2 wks. Alternative schedules of chlorambucil enable the administration of higher total chlorambucil doses, and have better antileukemia activity. So far, evidence on the feasibility of combining obinutuzumab with alternative chlorambucil schedules is lacking. We performed this retrospective analysis to analyze real life outcomes in chronic lymphocytic leukemia patients receiving a combination of obinutuzumab with different chlorambucil schedules. Methods: This was a retrospective survey performed in order to analyze the feasibility and efficacy of different obinutuzumab and chlorambucil combinations in a real-life setting. Patients receiving this combination as a front-line therapy for chronic lymphocytic leukemia in participating centers, outside of clinical trials, in 2017 and 2018 were included. Results: Seventy-three patients fulfilling entry criteria were identified. Their median age was 76 years, and ranged from 58 to 90 years. The median follow up time was 59 months. The response rate was 89%, with a median progression-free survival time of 27 months, and an overall survival time of 49 months. Chlorambucil was administered as planned in 15 of the 22 (79%) patients treated with chlorambucil pulses every 2 weeks; in 15 of the 42 (34%) patients treated with 7-day courses of chlorambucil administered every 4 weeks; and in 0 of the 10 patients treated with a continuous high dose of chlorambucil (p = 0.002). Changes in treatment schedules were made due to side effects. The progression-free and overall survival rates were similar between the three groups. Conclusions: The combinations of obinutuzumab with more intensive chlorambucil schedules are less feasible, preventing the administration of the intended higher total dose of chlorambucil, and do not improve outcomes in comparison to chlorambucil pulses administered every 2 weeks.